ERYTHROCYTOSIS IN CHILDREN: CASE REPORT - Teja Leban; Janez Jazbec (Slovenska pediatrija)

(untitled)
Erythrocytosis is a condition characterized by an increased mass of red blood cells, which manifests as an elevated concentration of hemoglobin, increased count of red blood cells, and increased hematocrit levels. It is important to distinguish erythrocytosis from polycythemia, which refers to an increase in all three types of blood cells. Thus, the term polycythemia is often incorrectly used as a synonym for erythrocytosis. In this article, we discuss a clinical case of erythrocytosis, provide a classification of different types of erythrocytosis, outline the diagnostic approach, and review the treatment options for managing erythrocytosis in children.